The transcription factor Pou4f3 is essential for the survival of postnatal and adult mouse cochlear hair cells and normal hearing - Singh, Jarnail; Randle, Michelle R.; Walters, Bradley J.; Cox, Brandon C. (Frontiers in Cellular Neuroscience, 2024)
Introduction Hair cells (HCs) of the cochlea are responsible for sound transduction and hearing perception in mammals. Genetic mutations in the transcription factor Pou4f3 cause non-syndromic autosomal dominant hearing loss in humans (DFNA15) which varies in the age of onset depending on the individual mutation. Mouse models with germline deletion or mutations in Pou4f3 have previously demonstrated its critical role in the maturation and survival of cochlear HCs during embryonic development. However, the role of Pou4f3 in auditory function and in the survival or maintenance of cochlear HCs after birth and during adulthood has not been studied. Methods Therefore, using the inducible CreER-loxP system, we deleted Pou4f3 from mouse cochlear HCs at different postnatal ages, relevant to specific stages of HC maturation and hearing function. Results and discussion Elevated auditory brainstem response thresholds and significant HC loss were detected in mice with Pou4f3 deletion compared to their control littermates, regardless of the age when Pou4f3 was deleted. However, HC loss occurred more rapidly when Pou4f3 was deleted from immature HCs. Additionally, HC loss caused by Pou4f3 deletion did not affect the number of cochlear supporting cells, but caused a delayed loss of spiral ganglion neurons at 4 months after the deletion. In conclusion, Pou4f3 is necessary for the survival of cochlear HCs and normal hearing at all postnatal ages regardless of their maturation state. Our data also suggest that Pou4f3 indirectly regulates the survival of spiral ganglion neurons.